2009
DOI: 10.1021/jp906039t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of the Low Resistivity TiSi2 Nanowires Grown with TiF4 Precursor

Abstract: Low-resistivity TiSi2 nanowires were synthesized on silicon with TiF4 precursor and without catalysts. The growth was found to follow vapor−solid mechanism. The single crystalline nanowires are of C54−TiSi2 phase with the diameters and lengths being 20−50 nm and 1−2 micrometers, respectively. The field emission properties of the TiSi2 nanowires were measured, and the turn on voltage is 8 V/μm when the current density attained 1 μA/cm2. The field enhancement factor is about 800 with the measured work function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…In previous works, several sets of experimental evidence also indicated that silicide nanowires were fabricated by a vapor-solid mechanism. 26,27 In our cases, no catalyst particles were found on the tip of the nanowires, suggesting that our nanowire growth was not via the typical vapor-liquid-solid growth mechanism. 28 The growth processes of the iron silicide nanowires included two steps.…”
Section: Methodsmentioning
confidence: 61%
“…In previous works, several sets of experimental evidence also indicated that silicide nanowires were fabricated by a vapor-solid mechanism. 26,27 In our cases, no catalyst particles were found on the tip of the nanowires, suggesting that our nanowire growth was not via the typical vapor-liquid-solid growth mechanism. 28 The growth processes of the iron silicide nanowires included two steps.…”
Section: Methodsmentioning
confidence: 61%
“…FeSi nanowires were fabricated in a high reaction concentration environment, while β-FeSi 2 nanowires were fabricated in a low one. Lots of experimental evidence indicates that the mechanism of the nanowires’ fabrication is a vapor-solid mechanism [32]. In our case, there were no catalyst particles or metal liquid droplets found on the tip of the nanowires, suggesting that the growth mechanism in our experiment was not a vapor-liquid-solid mechanism.…”
Section: Resultsmentioning
confidence: 60%
“…It is an active precursor in synthesizing thin films of metal fluorides and titanium silicate. 1,2 When TiF 4 is added to TiO 2 nanocrystals, photocatalytic hydrogen production is enhanced due to a change in surface morphology. 3 Moreover, the TiF 4 additive has shown superior catalytic activity in the decomposition of MgH 2 , Mg(BH 4 ) 2 , and Mg(AlH 4 ) 2 used in hydrogen storage applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…TiF 4 has been widely used in many technological applications. It is an active precursor in synthesizing thin films of metal fluorides and titanium silicate. , When TiF 4 is added to TiO 2 nanocrystals, photocatalytic hydrogen production is enhanced due to a change in surface morphology . Moreover, the TiF 4 additive has shown superior catalytic activity in the decomposition of MgH 2 , Mg­(BH 4 ) 2 , and Mg­(AlH 4 ) 2 used in hydrogen storage applications. By the application of a constant shear stress to TiF 4 additives, Ti 4+ is reduced to Ti 3+ and Ti 2+ during mechanochemical processing .…”
Section: Introductionmentioning
confidence: 99%